Examining a research and evaluation capacity building partnership: A systems approach - Tobin, Rochelle Amy (Curtin University, 2022)
This study took a systems approach to examine the WA Sexual Health and Blood-borne Virus Applied Research and Evaluation Network (SiREN). SiREN is a Curtin-based partnership between sexual health and blood-borne virus researchers, service providers and policymakers that aims to strengthen evidence-informed policy and practice. Findings demonstrate how a partnership-based approach can foster the development of trusting and responsive relationships leading to increased research and evaluation capacity and evidence-informed decision making.